One woman's construction of self and meaning. A qualitative study of the life of Alice Koller based on her autobiographical texts: "An Unknown Woman" (1981) and "The Stations of Solitude" (1990). - Litchfield, Diane Marie Quilty. (University of Ottawa (Canada), 1997)
This research project is a qualitative interpretation of the life of an American woman, Alice Koller, born in the mid-1920's, who described her construction of self and meaning in two texts, An Unknown Woman (1981) and The Stations of Solitude (1990). Within the framework of qualitative research, the autobiographical text provides an appropriate document through which to study an individual woman's reflections on her changing construction of self and meaning over her lifetime and within her specific socio-cultural and psychological contexts. The long term objective to which this project hopes to contribute is the development of our understanding and broadening of our appreciation of how those twentieth-century women who have written about their lives make meaning in their lives and transform their construction of self. This contextualized study will seek to answer two interrelated questions posed of Koller's texts. Firstly, against the conceptual framework of the major psychological research which seems to bear on her development, what was the nature of Alice Koller's transformational crisis, at age 37, on Nantucket Island; and, how did Koller change her construction of self and meaning during this transformational process? Secondly, situated within her socio-cultural context, how did Alice Koller respond to the conflicting ideals and images facing an educated woman in twentieth-century America? (Abstract shortened by UMI.)
Keywords: Biography.